IMPLEMENTASI RETRIBUSI DAERAH PELAYANAN KESEHATAN DI UPTD KESEHATAN PUSKESMAS PUSPO - Aminullah Aminullah; Dwi Mita Setyasih (Journal Publicuho, 2021)
This study discusses the implementation of the Retribution areas of health service in the UPTD Health Center Puspo. The objectives of this study are: 1). To find out the implementation process of Retribution Area of health service in UPTD Health Puspo. 2). To know the factors that influence in its implementation. The method used in this research is qualitative method. With qualitative methods we can describe the regional levy for health services and the factors that influence the implementation of the levy. The results of the study showed that the implementation of regional levy has not been effective. Efforts that need to be made by local governments in order to effectively implement. The effectiveness of service levy in Puskesmas Puspo must be done according to the applicable rules.